CAUSES AND CONSEQUENCES OF THE DETERIORATION OF THE ECOLOGICAL SITUATION IN UZBEKISTAN (European Journal of Interdisciplinary Research and Development, 2025)
The article talks about ecology, the concept of nature, the impact of the aggravation of the ecological situation on the decrease of the population's income, the impact of environmental degradation on human health, today's statistical indicators, ongoing work, plans.